Genomic epidemiology of clinical Campylobacter spp. at a single health trust site. Issue 10 (11th October 2018) - Dunn, Steven J.; Pascoe, Ben; Turton, James; Fleming, Vicki; Diggle, Mathew; Sheppard, Samuel K.; McNally, Alan; Manning, Georgina
Abstract : Campylobacter is the leading cause of bacterial enteritis in the developed world, and infections with the organism are largely sporadic in nature. Links between sporadic cases have not been established, with the majority of infections thought to be caused by genetically distinct isolates. Using a read-mapping approach, 158 clinical isolates collected during 2014 from the greater Nottinghamshire area were analysed to assess the local population structure and investigate potential case linkages between sporadic cases of campylobacteriosis. Four instances (2.5 %) of case linkage were observed across the dataset. This study demonstrates that case linkage does occur between sporadic Campylobacter infections, and provides evidence that a dual multi-locus sequence typing/within-lineage single nucleotide polymorphism typing approach to Campylobacter genomic epidemiology provides a benefit to public-health investigations.